EXTRACTION AND PURIFICATION OF PYOVERDINE PRODUCE BY LOCALLY ISOLATED Pseudomonas fluorescens And Its Ability As A Biological Control Agent - Khazaal, Ali; Shawkat, Muayad; AL-Shalchi, Sahar (Iraqi Journal of Science, 2024)
Pyoverdine was extracted from the local isolate ( PFAS14 ) after 10 hours of incubation time and reached maximum production after 46 hours.The extraction of pyoverdine was done as ferric-pyoverdine complex by organic solvent and precipitate with salt then purify with ion exchange and gel filteration chromatography.The maximum absorbance of pyoverdine was at 370 nm., while the maximum absorbance of ferric-pyoverdine complex was at 400nm. The pyoverdine showed inhibition activity against pathogenic fungi, bacteria and C. albicans, the supernatant of (PFAS14) isolate was also active while the ferric-pyoverdine complex does not show any activity.Curring the plasmid of PFAS14 isolate do not effect the production of pyoverdine and this confirms that the structural and regulator genes responsible for pyoverdine production were mediate by chromosome.